Comprehensive Assessment for Liquefaction Vulnerability in Indonesia: Empirical and Element Simulation Approaches - Fitri, Siti Nurlita; Sawada, Kazuhide (Salehan Institute of Higher Education, 2025)
Historical liquefaction events have occurred at many locations, such as Yogyakarta and Lombok; the most significant flow side is in Palu. The standard Indonesian liquefaction assessment is based on a simplified empirical analysis. However, these methods only occasionally yield appropriate results. Contrastingly, the limited data from the cyclic test ensured that the liquefaction ratio could only partially support the liquefaction vulnerability. This research aims to re-examine the empirical approach that combines the constitutive model using LIQCA with a cyclic triaxial test (CXT) and cyclic simple shear (CSS). The empirical method was arranged using deterministic and probabilistic approaches, and the recommendation of the peak ground acceleration (PGA) threshold was validated. The results show a strong relationship between all calculation methods and the SPT value, which differs in the liquefaction strength ratio. This output offers the PGA recommendation results, reaching a 48% overestimation from the empirical method without considering the cyclic test. This research presents the development of a combination of the empirical method with the element simulation from CXT and CSS. This offers a comprehensive overview of the Indonesian requirement standard assessment for liquefaction vulnerability analysis. Doi: 10.28991/CEJ-2025-011-01-019 Full Text: PDF